2010
DOI: 10.1890/09-1172.1
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis for ecosystem recovery following rodent eradication and seabird restoration in an island archipelago

Abstract: Invasive species are widespread and can have devastating effects on biota, especially insular biota. Invasive species eradications are increasingly employed to promote island recovery to preinvasion states. However, it remains unclear if additional restoration actions may be required on islands that were once heavily reliant on seabird guano for ecosystem functions. Active seabird augmentation has been suggested as necessary to exact ecosystem recovery on contemporary timescales in some cases. I use two experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 37 publications
5
76
0
Order By: Relevance
“…Some species naturally recolonized abandoned breeding colonies or habitats from which they had been extirpated [42,43], whereas others needed assisted re-introduction [42] or formed new colonies at suitable sites [41]. In some cases, eradication of rats, foxes, raccoons or other humanintroduced predators was necessary to restore seabird colonies [42,44]. Another important factor in the recovery of many birds was the ban of DDT during the 1970s [40].…”
Section: Birdsmentioning
confidence: 99%
“…Some species naturally recolonized abandoned breeding colonies or habitats from which they had been extirpated [42,43], whereas others needed assisted re-introduction [42] or formed new colonies at suitable sites [41]. In some cases, eradication of rats, foxes, raccoons or other humanintroduced predators was necessary to restore seabird colonies [42,44]. Another important factor in the recovery of many birds was the ban of DDT during the 1970s [40].…”
Section: Birdsmentioning
confidence: 99%
“…Invasive species are detrimental to native island species, communities, and ecosystems (Blackburn et al 2004;Kurle et al 2008;Jones 2010). Rats (Rattus spp.)…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an increase in burrow density and distribution after rat eradication may reflect a rapid change in soil dynamics. It has been postulated that a burrow density of 0.3-1 burrow/m 2 is needed to promote ecosystem recovery to never-invaded levels Jones 2010a). We found that mean burrow density on restored islands was less than half (<0.1 burrow/m 2 ) that on the never-invaded Ruamaahuanui (>0.2 burrow/m 2 ).…”
Section: Conservation Implicationsmentioning
confidence: 56%
“…Because petrels engineer island habitat, population response will likely play a disproportionately large role in the recovery of ecosystem functioning. Yet only now are factors driving petrel colony recovery being studied (Jones 2010a;Buxton et al 2014).…”
Section: Introductionmentioning
confidence: 99%